The Scientic Heritage of V.N. Chekmonas (1936–2004): Old Believers in Lithuania - Морозова, Надежда (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] One of the most important spheres of scientific interests of Professor V.N. Chekmonas (1936–2004) of the last decade of his life was the study of the Old Believers of Lithuania. As a professional dialectologist, he was primarily interested in Old Believers’ dialects. In 1996–2002, Chekmonas organized more than 10 expeditions to all areas of compact residence of the Old Believers in Lithuania, border regions of Latvia and Belarus as well as the Opochetsky district in the Pskov region. During this time, more than 120 settlements were surveyed, and a collection of tape recordings of Old Believers’ dialects of Lithuania was created. This collection contains approximately 400 hours of tape recordings; it now is digitized and stored at the Archive of Dialects of the Research Center of Geolinguistics at the Institute of Lithuanian Language in Vilnius.